Infrared absorption in Li-intercalated tungsten oxide - Larsson, Anna-Lena (2007)
Thin films of amorphous and polycrystalline tungsten oxide, were produced by reactive dc magnetron sputtering and nanocrystalline films were deposited by advanced gas evaporation. The films were submitted to electrochemical intercalation of Li ions before infrared reflectance measurements were carried out. For crystalline films the reflectance in the wavelength region 10-30 µm increases upon intercalation, indicating an increasing free electron contribution. On the other hand, all the films display an increased absorption at wavelengths less than 10 µm when intercalated. The thermal emittance could be varied from about 0.5 to 0.7-0.75 by intercalation in films with thicknesses in excess of 1 µm. Both absorption and interference contribute to the emittance contrast.